Utilizing Internet Analysis Technology to Conduct Data Analysis of Student Attitude Survey - Yongcheng Cao; Quanguo Liu; Huajie Chen (International Journal of Informatics and Information Systems, 2023)
Language attitude is people’s understanding and evaluation of languages, which has an important effect on language learning. Based upon investigation into 605 Tibetan college students from 5 colleges in Tibet areas, and combined with network data, this paper mainly analyzes their attitude towards Tibetan, Chinese and English from four dimensions: recognizing, instrumental, integrative and transferring attitude. This paper also discusses the relationship between students’ language attitude and their gender and grade. This study utilizes internet analysis technology to analyze data obtained from a student attitude survey. The survey was conducted to examine the attitudes of students towards a particular educational program. The study includes a description of the survey instrument and the method used to collect data. The data collected was analyzed using various statistical techniques, including frequency analysis and correlation analysis. The findings reveal important insights into student attitudes towards the program and highlight areas of improvement for the program. The use of internet analysis technology proved to be an efficient and effective method of data analysis in this study. The study contributes to the growing body of knowledge on data analysis in educational research and provides useful information for educators and policymakers.